The meaning of Russia’s transport and logistics in expanding integration processes - T. A. Goroshnikova; O. I. Donde (Мир новой экономики)
The paper considers the role and tasks of the transport industry in the economic complex of Russia in the economic sanctions imposed. The analysis of the predicted changes in the international transport and logistics complex allowed the staging recommendations for amendments to the basic policy documents for the industry growth. Also, the paper substantiates the need to adjust certain points in the development of logistics projects within Russia and the Eurasian Economic Union (EEU). The authors analyzed the meaning of railway transport, which is the primary carrier of the considered commodity groups (products of the metallurgical, logging, coal industry) in the new economic conditions.The research proposed the calculation of the projected increase in rail freight trafﬁc in the Siberian Federal District and the Far Eastern Federal District. This assessment is based on the analysis of external exports of the Russian Federation and the Republic of Belarus in the logging, metallurgical, and coal industries in 2020 and a valuation of the sanctions’ impact on foreign trade activity.